CD11c- and CD11b-expressing mouse leukocytes transport single Toxoplasma gondii tachyzoites to the brain - Courret, Nathalie; Darche, Sylvie; Sonigo, Pierre; Milon, Geneviève; Buzoni-Gâtel, Dominique; Tardieux, Isabelle (Blood, 2006)
The protozoan parasite Toxoplasma gondii enters hosts through the intestinal mucosa and colonizes distant tissues such as the brain, where its progeny persists for a lifetime. We investigated the role of CD11c- and CD11b-expressing leukocytes in T gondii transport during the early step of parasitism from the mouse small intestine and during subsequent parasite localization in the brain. Following intragastric inoculation of cyst-containing parasites in mice, CD11c+ dendritic cells from the intestinal lamina propria, the Peyer patches, and the mesenteric lymph nodes were parasitized while in the blood, parasites were associated with the CD11c- CD11b+ monocytes. Using adoptive transfer experiments, we demonstrated that these parasitized cells triggered a parasitic process in the brain of naive recipient mice. Ex vivo analysis of parasitized leukocytes showed that single tachyzoites remained at the cell periphery, often surrounded by the host cell plasma membrane, but did not divide. Using either a dye that labels circulating leukocytes or an antibody known to prevent CD11b+ circulating leukocytes from leaving the microvascular bed lumen, and chimeric mice in which the hematopoietic cells expressed the green fluorescent protein, we established that T gondii zoites hijacked CD11b+ leukocytes to reach the brain extravascular space.